Literary Practice according to Michel Henry: A Philosophical Introduction to his Novels - Jean-Baptiste Dussert (Journal of French and Francophone Philosophy, 2012)
Although the author of four novels, Michel Henry never produced an aesthetics of literature. The purpose of this article is, after a presentation of his philosophy of immanence and his concept of life, to locate where the literary practice takes place in his system. In this study, we are not interested in the poetic quality of his works, but in the possibility to base his singular creativity on his philosophical reflection. This leads us to insert literature in the vast phenomenon of culture and ethics, and to grasp the function of poetics in the struggle against barbarism.